2015
DOI: 10.3928/01484834-20150218-21
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the Primary Care Workforce: A Study of Nurse Practitioner Students’ Plans After Graduation

Abstract: Primary care is a growing area, and nurse practitioners (NPs) hold promise for meeting the need for additional providers. This article reports on the future plans of more than 300 primary care NP students in family, adult, and adult gerontology programs. The sample was obtained through NP faculty, and data were collected via an online survey. Results indicated that although these students chose primary care, only 48% anticipated working in primary care; 26% planned to practice in rural areas, and 16% planned t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…One study of novice NPs in primary care ( n = 177) reported mentorship, professional development and role support as facilitators of this transition [ 50 ]. Further, positive clinical experience and perceptions of mentorship and preceptors were identified as some of the top predictors of NP students choosing to work in primary care [ 77 ]. As a result of growing evidence, the US National Academy of Medicine has recommended establishing accredited and standardised postgraduate training for primary care providers, including NPs [ 78 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study of novice NPs in primary care ( n = 177) reported mentorship, professional development and role support as facilitators of this transition [ 50 ]. Further, positive clinical experience and perceptions of mentorship and preceptors were identified as some of the top predictors of NP students choosing to work in primary care [ 77 ]. As a result of growing evidence, the US National Academy of Medicine has recommended establishing accredited and standardised postgraduate training for primary care providers, including NPs [ 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…At the organisational level, the practice environment can serve as a facilitating factor, as evidenced by US rural NPs, who are more likely than their urban counterparts to manage their patient care as primary care providers independently [ 29 , 49 , 110 ]. At a personal level, professional development opportunities, institutional commitment to ongoing education, work-life balance, mentorship, autonomy, ability to use clinical assessment and decision-making skills [ 57 , 77 , 90 , 98 ] are additional factors that help attract and keep NPs in primary care practice.…”
Section: Discussionmentioning
confidence: 99%
“…Eleven articles considered regulatory changes to improve rural nursing and allied health workforce recruitment and retention. Of these, eight considered scope of practice and new roles to deal with intractable rural workforce shortages, while the remainder evaluated overseas recruitment (, Table 4.3) 43-53 …”
Section: Resultsmentioning
confidence: 99%
“…A greater emphasis on gerodontological learning experiences during clinical placements has the potential to positively impact on future practice. Internationally, graduates who received gerodontology education have been found more likely to consider working with aged-care communities (Abbey et al, 2006;Budd et al, 2015). However, Nilsson et al (2018) identified a paucity of research in this area for the undergraduate dental curricula in Australia and found that clinical exposure to aged-care oral health at an undergraduate level could positively influence student learning outcomes.…”
Section: Introductionmentioning
confidence: 99%